2013
DOI: 10.1158/1541-7786.mcr-13-0292
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Screen Identifies miRNAs That Target RAD51 and RAD51D to Enhance Chemosensitivity

Abstract: Homologous recombination (HR) mediates error-free repair of DNA double-strand breaks (DSBs). RAD51 is an essential protein for catalyzing HR and its recruitment to DSBs is mediated by many factors including RAD51, its paralogs, and breast/ovarian cancer susceptibility gene products BRCA1/2. Deregulation of these factors leads to impaired DNA repair, genomic instability, and cellular sensitivity to chemotherapeutics like cisplatin and poly (ADP-ribose) polymerase (PARP) inhibitors. microRNAs (miRs) are short, n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 51 publications
2
65
0
Order By: Relevance
“…26 miR-103 and miR-107 directly targeted RAD51, which was an essential protein for catalyzing HR repair of DNA double-strand breaks (DSBs). 27 Additionally, another critical component of non-homologous end joining (NHEJ) for DSBs repair-Ku80, was a direct target of miR-526b. Our data unraveled that A549 cells with miR-33b-3p overexpression exhibited lower levels of gH2A.X under cisplatin treatment, indicating that miR-33b-3p promoted DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…26 miR-103 and miR-107 directly targeted RAD51, which was an essential protein for catalyzing HR repair of DNA double-strand breaks (DSBs). 27 Additionally, another critical component of non-homologous end joining (NHEJ) for DSBs repair-Ku80, was a direct target of miR-526b. Our data unraveled that A549 cells with miR-33b-3p overexpression exhibited lower levels of gH2A.X under cisplatin treatment, indicating that miR-33b-3p promoted DNA damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the availability of the building blocks, the cinnamide analogues (B) were also constructed by Heck coupling of the corresponding aromatic bromide with acrylamide C. After introducing motif 1 as an amine through amide coupling (D to E), the intermediates were cyclized under mild dehydration conditions with iodine and hexamethyldisilazine 18 to give the desired quinazolinone products (F). In this way, one series of compounds incorporated alkyl and cycloalkyl substituents (1)(2)(3)(4)(5)(6)(7)(8), and another series contained substituted aromatics with a variable spacer -(CH 2 )n-(n =0-2, 9-27). The latter series was designed to optimally target residues F195 and Y191 through piinteractions.…”
Section: Ar T Ic Le In F O Abstractmentioning
confidence: 99%
“…RAD51 has been recognized as a potential oncotarget due to its critical role in HR, and contributes to an aggressive cellular phenotype and resistance to therapeutics. Several small molecule RAD51 inhibitors have been discovered by high-throughput screening of compound libraries, notably B02 [5][6][7] , the RI series [8][9][10] and the IBR2 series 11,12 ( Figure 1). Alternatively, a fragmentbased screening approach at Cambridge identified another series of compounds 13,14 ( Figure 1).…”
mentioning
confidence: 99%
“…It has recently been shown that miR-22, miR-93, miR-106b, miR-451 were aberrantly expressed in the serum of ovarian cancer patients (Ji et al, 2014). There is rapidly accumulating evidence suggesting that miR-103 and miR-107 restore sensitivity of resistant ovarian cancer cells to chemotherapeutic drugs via targeting of RAD51 and RAD51D Huang et al (2013). It has previously been shown that enhancer of zeste 2 (EZH2) promoted cellular proliferation and enhanced invasive potential of epithelial ovarian cancer cells (Li et al, 2010).…”
Section: Generalmentioning
confidence: 99%